Contribution teacher student relationship, quality of friendship and self esteem as mediator to students social skills in madrasah - Ecep Supriatna; Dona Fitri Annisa (Jurnal Konseling dan Pendidikan, 2026)
This study examines a structural model of students’ social skills among Madrasah Aliyah students by investigating the roles of teacher–student relationships and friendship quality, with self-esteem serving as a mediating variable. Guided by Social Cognitive Theory, the study addresses the limited empirical evidence regarding the simultaneous contribution of school-based interpersonal factors and individual psychological factors in predicting social skills within the context of Islamic secondary education. A quantitative approach was employed using Structural Equation Modeling (SEM). Data were collected from 425 students of Madrasah Aliyah Negeri 2 Bandung selected through random sampling, representing all grade levels. The findings revealed that the proposed model demonstrated an acceptable level of fit and supported the hypothesized relationships among the variables. Teacher–student relationships and friendship quality significantly predicted students’ social skills both directly and indirectly through self-esteem. Self-esteem also functioned as a significant mediator, indicating that positive interpersonal experiences in school contribute to the development of social skills by enhancing students’ self-worth. These findings highlight the importance of fostering supportive teacher–student interactions and high-quality peer relationships to strengthen students’ social competencies in madrasah settings. The study contributes to the literature by integrating interpersonal and psychological factors into a single explanatory model